Landslide Size Distribution Characteristics of Cretaceous and Eocene Flysch Assemblages in the Western Black Sea Region of Turkey - Akgun, Aykut; Gorum, Tolga; Nefeslioglu, Hakan A. (Springer International Publishing, 2020)
The main purpose of the study is to determine the general characteristics of the landslide sizes observed in Cretaceous and Eocene aged flysch assemblages at the Western Black Sea region of Turkey by using magnitude and frequency relations. For this purpose, the magnitude and frequency relations were investigated by considering power-law scaling characteristics of the geological formations. The probability distributions were also examined by considering Double Pareto and Inverse Gamma distribution models. According to the power-law relations, the rollover effects were observed at 0.047 and 0.048 km2, and the fractal dimensions of the distributions were obtained as −1.97 and −1.41 for Cretaceous and Eocene flysch assemblages, respectively. Considering the probability distributions, the best-fits were acquired from the models Double Pareto with three parameters estimated by maximum likelihood estimation for Cretaceous flysch and Kernel density estimation for Eocene flysch. When we compared these results with the results of a study carried out in the same flysch but in another sub-catchment, it is concluded that rollover effects and fractal dimensions may not be generalized, that means, the parameters may differ site to site depending on not only spatial resolution but also morphological, climatic, and anthropogenic features of the region in concern, and conversely, landslide size distributions fit Double Pareto distribution models in general.